The Use of Solanum Incanum for Water Treatment at Household Level, a Case of Namilyango Village Kisenyi Cell in Mukono District - Wilberforce Bwambale (Uganda Christian University, 2025)
Access to clean and safe water remains a challenge as people depend on water from unprotected water sources for domestic use and consumption. This study aimed at the use of Solanum Incanum as a natural disinfectant for water treatment at household level, focusing on Nakyijeera Spring in Namilyango Village. Water quality assessment was carried out in dry and wet seasons with water samples collected in the morning, afternoon and evening. In both seasons, the spring water consistently showed Turbidity, Colour and Total iron values of 0 NTU, 0 PtCo and 0.07±0.00 mg/l respectively. pH ranged from 6.27 to 6.57 and 6.73 to 6.80 in the dry and wet seasons respectively. In the dry season, E. coli values showed 19 CFU/100ml, 14 CFU/100ml, and 14 CFU/100ml, and Total Coliforms of 44 CFU/100ml, 27 CFU/100ml, and 31 CFU/100ml in the morning, afternoon and evening respectively. In the wet season, E. coli of 21 CFU/100ml, 21 CFU/100ml, and 22 CFU/100ml, and Total Coliforms of 48 CFU/100ml, 38 CFU/100ml, and 42 CFU/100ml in the morning, afternoon and evening respectively. The optimum contact time was achieved at 45 minutes, with an optimum dosage of 40ml/l, showing 87% E. coli removal and 86.5% Total Coliform removal. The prototype designed for water treatment showed reduction values of E. coli to 2 CFU/100ml, and 5 CFU/100ml for Total Coliforms. This thus illustrated that Solanum Incanum can be used effectively for water disinfection at household level.